PENERAPAN MODEL PEMBELAJARAN GENERATIF UNTUK MENINGKATKAN AKTIVITAS BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 11 KOTA BENGKULU - Dianti, Aisyah; Rusdi, Rusdi; Yensy, Nurul Astuty (JP2MS, 2020)
The aim of this research was to know how to manage the class with applying generative learning model improving student learning activity in mathematics Grade VIII Junior High School Number 11 Bengkulu City. The design of this research was classroom action research with four steps were: planning, acting, observing and reflecting. The subject of this research was 32 students of Grade VIII B Junior High School Number 11 Bengkulu City on academic year 2018/2019. Data collection was done by using student learning activity observation sheet. Class management with applying generative learning model improved student learning activity by: the exploration phase trained student to listen explaining, pay attention and express opinion; the focus phase trained student to team up, discuss, drawing and writing; the challenge phase trained student to solve the problem and active on class discussing; and the application phase trained student to do exercises. The result of average score in sudent learning activity improved from first cycle to third cycle: 19,50; 23,75; 28,38.